FACTORS AFFECTING ACCIDENTS ON SKI HILLS (Slovenian Case) - Janez Mekinc; Lea Grom; Tomislav Omejec; Saša Planinc (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2017)
Safety on the licensed ski slopes in Slovenia, like in many other winter countries, is a complex notion involving, in addition to ski slope owners and operators, several governmental agencies and functionaries, such as inspectors, supervisors, police, medical staff, and others. We cannot assign blame for accidents to them. Our research, in agreement with the Inspectorate of the Republic of Slovenia responsible for Internal Affairs and the Police Academy, focuses on the causes for skiing accidents. We found out that a skier plays an important role in safe-guarding his/her own safety as well as that of fellow skiers on the ski slope. Obligations of the skier using a licensed ski slope are described in 10 internationally endorsed FIS rules of skiing. We obtained data on ski accidents for three consecutive ski seasons between December 2012 and April 2015. We studied whether or not the skiers followed FIS regulations and whether or not they adequately safeguarded their own safety. We also studied who is most often responsible for ski accidents.